Financial Impact of the Robotic Approach in Liver Surgery: A Comparative Study of Clinical Outcomes and Costs Between the Robotic and Open Technique in a Single Institution - Daskalaki, Despoina (J Laparoendosc Adv Surg Tech A, 2017)
Background: One of the perceived major drawbacks of minimally invasive techniques has always been its cost. This is especially true for the robotic approach and is one of the main reasons that has prevented its wider acceptance among hospitals and surgeons. The aim of our study was to evaluate the clinical outcomes and economic impact of robotic and open liver surgery in a single institution. Methods: Sixty-eight robotic and 55 open hepatectomies were performed at our institution between January 1, 2009 and December 31, 2013. Demographics, perioperative data, and postoperative outcomes were collected and compared between the two groups. An independent company performed the financial analysis. The economic parameters comprised direct variable costs, direct fixed costs, and indirect costs. Results: Mean estimated blood loss was significantly less in the robotic group (438 versus 727.8 mL; P = .038). Overall morbidity was significantly lower in the robotic group (22% versus 40%; P = .047). Clavien III/IV complications were also lower, with 4.4% in the robotic versus 16.3% in the open group (P = .043). The length of stay in the intensive care unit (ICU) was shorter for patients who underwent a robotic procedure (2.1 versus 3.3 days; P = .004). The average total cost, including readmissions, was $37,518 for robotic surgery and $41,948 for open technique. Conclusions: Robotic liver resections had less overall morbidity, ICU, and hospital stay. This translates into decreased average costs for robotic surgery. These procedures are financially comparable to open resections and do not represent a financial burden to the hospital.